2017
DOI: 10.1007/s10143-017-0828-x
|View full text |Cite
|
Sign up to set email alerts
|

Intradiploic pseudomeningocele and ossified occipitocervical pseudomeningocele after decompressive surgery for Chiari I malformation: report of two cases and literature review

Abstract: Intradiploic cerebrospinal fluid (CSF) collections are rare findings. The authors describe two pediatric patients with iatrogenically induced occipital CSF collections after decompressive surgery for Chiari I malformation. The first patient presents a large occipital intradiploic pseudomeningocele and the second patient an intradiploic pseudomeningocele merging with an ossified occipitocervical pseudomeningocele. Though being rarities after decompression for Chiari I malformation, intradiploic fluid collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…7 8 9 When this fails, there occurs accumulation of CSF within the diploe, leading to widening of outer and inner tables due to the water-hammer effect of CSF accumulations. 2 In the present case, the pseudomeningocele is probably a result of shunt malfunction followed by increased CSF pressure, leading to accumulate CSF in the extradural space.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…7 8 9 When this fails, there occurs accumulation of CSF within the diploe, leading to widening of outer and inner tables due to the water-hammer effect of CSF accumulations. 2 In the present case, the pseudomeningocele is probably a result of shunt malfunction followed by increased CSF pressure, leading to accumulate CSF in the extradural space.…”
Section: Discussionmentioning
confidence: 58%
“…Pseudomeningocele refers to CSF collections in cavities within the soft tissues or localized in calvarial bone diploe. 2 Pseudomenigocele can be congenital (nontraumatic) or traumatic. 3 4 The traumatic cause can be blunt trauma, inadvertent trauma to the dura, planned dural opening (surgery/ iatrogenic), infection, or intramural hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that in addition to the child in the present case, 6 patients with Chiari I malformation have been described thus far who postoperatively devel-oped an occipital intradiploic pseudomeningocele. 18,19 Three of these patients had undergone surgery with duraplasty, 3,11,23 and 3 without dural closure. 18,19 To the best of our knowledge we present here the first report of a patient who initially developed an occipital intradiploic pseudomeningocele and then a de novo cervical syrinx following decompressive surgery for Chiari I malformation.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Three of these patients had undergone surgery with duraplasty, 3,11,23 and 3 without dural closure. 18,19 To the best of our knowledge we present here the first report of a patient who initially developed an occipital intradiploic pseudomeningocele and then a de novo cervical syrinx following decompressive surgery for Chiari I malformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation